PENGARUH LATIHAN RUNNING UPHILL AND DOWNHILL TERHADAP POWER OTOT TUNGKAI PADA TIM BOLA BASKET PUTRI SMA N 11 PEKANBARU - Zesfi, Arif Rizki; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: problem this research is weaknes power of leg muscle from women basketball team sma n 11 pekanbaru , so make the player lose the ball if they on the offensive rebound or deffendsive rebound . This research purpose want to know the effect of running uphill and downhill toward the power of leg muscle of women basketball team of sman 11 pekanbaru. Forms of this research is the experimental treatment (Experimental), with sampel of 10 people. Were obtained and collected through the pree test and post test before and after running uphil and downhill excercise using isntrument vertical jump power test, which aims to measure the power of leg muscle. After that, the data is processed with statistical, normality test with lilifors test at significance level Î± (0.05). The hypothesis is the effect of exercise running uphill and downhill to the power of leg muscle. Based on t test analysis produces Ttabel Thitung of 10.29 and 1.812, meaning Thitung> Ttabel. Based on the analysis of statistical data, there are an average Pree-test of 8,63 and an average post-test 8,99, then the data is normal. Thus, there Effect of running uphill and downhill exercise toward the power of leg muscle of women basketball team of sman 11 pekanbaru.Keywords : Running Uphill And Downhill , The Power Of Leg Muscle